Preclinical Characterization of Antinociceptive Effect of Bergamot Essential Oil and of Its Fractions for Rational Translation in Complementary Therapy - Damiana Scuteri; Laura Rombolà; Michele Crudo; Chizuko Watanabe; Hirokazu Mizoguchi; Shinobu Sakurada; Kengo Hamamura; Tsukasa Sakurada; Paolo Tonin; Maria Tiziana Corasaniti; Giacinto Bagetta (MDPI AG, 2022)
Bergamot essential oil (BEO) is endowed with consistent and reproducible antinociceptive and anti-allodynic properties when administered via an inhalation route. However, the effects of its main constituents and of its decolored (DEC) and deterpenated (DET) fractions, which are enriched in limonene or in linalool and linalyl acetate, respectively, on spontaneous motor activity related to anxiety and on formalin-induced licking/biting biphasic behavior have never been investigated before. Therefore, the present research aims to characterize the role of BEO components on an experimental pain model that is relevant to clinical translation. Under our present experimental conditions, a paper filter disc soaked with different volumes of the phytocomplex and of its fractions that was applied at the edge of the observation chamber allowed the effects on the spontaneous motor activity and on the formalin-induced nocifensive response in ddY-strain mice to be studied. The present research demonstrated the effects of the DEC fraction of BEO on motor activity and on formalin-induced licking/biting behavior for the first time, proving that limonene is implicated in reduced motor activity and that it is important for the analgesic effect.